(untitled) (Research, Society and Development, 2022)
Arterial hypertension is characterized by an increase in blood pressure greater than or equal to 140/90 mmHg, directly linked to conditions such as metabolic and functional changes marked by one or more risk factors, such as obesity and Type II Diabetes Mellitus (T2DM). Thus, this qualitative and observational cross-sectional study aims to associate some aspects of hospital patients with Systemic Arterial Hypertension and its preponderance according to data from a UBS in Cascavel, Paraná, in addition to looking for aspects related to an inclination towards the development of SAH, selecting, through an appropriate classification, hospital patients to obtain the expected data, while comparing the information presented in the medical records and exams to the national data used as a reference base. In order to achieve these objectives, it is important to have a methodology that focuses on the description of the epidemiological profile of 51 hypertensive patients based on criteria such as: sex, age, associated diseases and the proper medical treatment for the patients in the period between January/2020 to December/2021. With a detailed review of the data collected for this research, it was possible to verify, therefore, a higher prevalence of females, as well as the higher incidence in the elderly population, especially in hospital patients with obesity and overweight, associated with the presence of T2DM.